Enhancing Growth, Yield, and Antioxidant Activity of Bitter Gourd (Momordica charantia L.) through Amino Acid Foliar Spray Application - Lamiaa El-Khayat; Mohssen Elbagory; Mohamed Elsadek; Nevin Ahmed; Ibrahim Mohamed; Alaa El-Dein Omara; Nesrein Salim (Horticulturae, 2023)
Bitter gourd has picked up noteworthy consideration for its pharmacological benefits. However, the impact of amino acids (AAs) dosage on growth, yield, and antioxidants is uncertain. In this study, we investigated the effects of foliar spraying bitter gourd with 100, 200, and 300 mg/L dosages of tryptophan (Trp), glutamine (Gln), and phenylalanine (Phe). The results revealed that Trp, at a dosage of 300 mg/L, produced the most substantial increase in plant length, followed by 300 mg/L Phe. Additionally, the highest values of the fresh dry weight of the plants, fresh weight of the first fruit, fruit number per plant, fresh weight of the fruits per plant, and total fruit output per hectare were seen at 300 mg/L of Trp, followed by 300 mg/L of Gln. Phe at 300 mg/L yielded the highest levels of total phenolics and total flavonoids, coupled with strong scavenging activity against 2,2-diphenyl-1-picrylhydrazyl. These outcomes show the potential of Trp and Gln foliar sprays to enhance bitter gourd growth, yield, and certain antioxidant compounds. These findings carry substantial implications for the enhancement of bitter gourd cultivation and quality. By revealing AA’s potential for improving bitter gourd, our research contributes to bolstering the agricultural sustainability of this remarkable crop.